A Factors Shaper The Character Of Buddhist Students At SMA Negeri 1 Donorojo : Factors Shaper student character - Jesyca Maya Nila; Hesti Sadtyadi; Widia Darma (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
This study aims to find out what are the factors that shape the character of Buddhist students at SMA Negeri 1 Donorojo. This research uses quantitative methods with a type of descriptive research factor analysis Exploratory factor Analysis (EFA). The subjects in this study were 62 Buddhist students at SMA Negeri 1 Donorojo. The data collection techniques used were observation, interviews and questionnaires. The results of data analysis showed KMO of 0.787 ≥ 0.5, Bartlett's Test of Sphericity of 1230.920, Measure Sampling Adequacy (MSA) of > 03 and Reliability of Cronbach's alpha instrument of 0.890 > 0.6. The results showed that there were twelve factors forming student character, namely positive will factors, family inattention factors, environmental support factors, inner voice or conscience factors, habit factors, positive hereditary factors, positive family factors, school environment factors, community environment factors, negative will factors and physical environment factors. Of the twelve factors, the most dominant and has the greatest eigenvalue of 8, 178 is the positive will factor. Cumulative percentage og variance of all data amounted to 76.259%. Keywords: Factors, Character, Buddhist Students